Agroforestry: An effective multi-dimensional mechanism for achieving Sustainable Development Goals - Goparaju, L.; Ahmad, F.; Uddin, M.; Rizvi, J. (Uniwersytet Mikolaja Kopernika, 2020)
The ecological footprint has far surpassed the biocapacity of our globe to fulfill the current requirement of the people living on the earth which needs sustainable vision with synergic alternative/option to meet the current human demand without compromising the need for the future generation. We examined the various SDGs goals with respect to agroforestry capacity and contribution based on available literature and knowledge. The study provides a better understanding of the synergic approach/strategies with retrospective and prospective ways for choosing agroforestry exercise which is an effective mechanism for providing multi-dimensional ecosystem services without interruption in achieving the majority of SDGs goals. The outcome of the evaluation highlights that agroforestry can contribute very significantly and can play a vital role in SDG-1, SDG-2, SDG-11, SDG-13, and SDG-15 directly in mitigating poverty, contributing towards food security, improving in creating a viable healthy city and in providing a sustainable overall prosperous environment in the prevailing climate change setup whereas indirectly it can serve others SDGs goals simultaneously that aim to provide better health and education, women empowerment, effective contribution towards clean water and energy for all sections of the society/citizen. The analysis further concluded although agroforestry has a vibrant future and hope it will get adequate priority in various countries with a focus on policy and investment.